DEVELOPMENT, EVALUATION AND CHARACTERISTICS OF OPHTHALMIC IN SITU GEL SYSTEM: A REVIEW - DEKA, MRINMOY; AHMED, ABDUL BAQUEE; CHAKRABORTY, JASHOBIR (International Journal of Current Pharmaceutical Research, 2019)
Eye is a sensitive organ and is easily injured and infected. Delivery of drugs into eye is complicated due to removal mechanism of precorneal area results decrease in therapeutic response. Conventional ocular delivery systems like solution, suspension, ointment shows some disadvantages such as rapid corneal elimination, repeated instillation of drug and short duration of action. In situ polymeric delivery system will help to achieve optimal concentration of drug at the target site, thereby helps to achieve the desired therapeutic concentration. There are various novel ocular drug delivery systems such as In-situ gel, dendrimers, niosomes, nanoparticulate system, collagen shield, ocular iontophoresis suspension and ocusert etc. In situ gelling systems are liquid upon instillation and undergo a phase transition to form gel due to some stimuli responses such as temperature modulation, change in pH and presence of ions. Various attempts have been made towards the development of stable sustained release in-situ gels. Newer research in ophthalmic drug delivery systems is directed towards an incorporation of several drug delivery technologies, that includes to build up systems which is not only extend the contact time of the vehicle at the ocular surface, but which at the same time slow down the removal of the drug. This is a review based on ocular in situ gels, characteristization, techniques and evaluation of in situ ophthalmic drug delivery systems,